T2 relaxation time is related to liver fibrosis severity - Guimaraes, Alexander R.; Siqueira, Luiz; Uppal, Ritika; Alford, Jamu; Fuchs, Bryan C.; Yamada, Suguru; Tanabe, Kenneth; Chung, Raymond T.; Lauwers, Gregory; Chew, Michael L.; Boland, Giles W.; Sahani, Duhyant V.; et al. (Quantitative Imaging in Medicine and Surgery; Vol 6, No 2 (April 28, 2016): Quantitative Imaging in Medicine and Surgery, 2016)
Background: The grading of liver fibrosis relies on liver biopsy. Imaging techniques, including elastography and relaxometric, techniques have had varying success in diagnosing moderate fibrosis. The goal of this study was to determine if there is a relationship between the T2-relaxation time of hepatic parenchyma and the histologic grade of liver fibrosis in patients with hepatitis C undergoing both routine, liver MRI and liver biopsy, and to validate our methodology with phantoms and in a rat model of liver fibrosis. Methods: This study is composed of three parts: (I) 123 patients who underwent both routine, clinical liver MRI and biopsy within a 6-month period, between July 1999 and January 2010 were enrolled in a retrospective study. MR imaging was performed at 1.5T using dual-echo turbo-spin echo equivalent pulse sequence. T2 relaxation time of liver parenchyma in patients was calculated by mono-exponential fit of a region of interest (ROI) within the right lobe correlating to histopathologic grading (Ishak 0–6) and routine serum liver inflammation [aspartate aminotransferase (AST) and alanine aminotransferase (ALT)]. Statistical comparison was performed using ordinary logistic and ordinal logistic regression and ANOVA comparing T2 to Ishak fibrosis without and using AST and ALT as covariates. (II) A phantom was prepared using serial dilutions of dextran coated magnetic iron oxide nanoparticles. T2 weighed imaging was performed by comparing a dual echo fast spin echo sequence to a Carr-Purcell-Meigboom-Gill (CPMG) multi-echo sequence at 1.5T. Statistical comparison was performed using a paired t-test. (III) Male Wistar rats receiving weekly intraperitoneal injections of phosphate buffer solution (PBS) control (n=4 rats); diethylnitrosamine (DEN) for either 5 (n=5 rats) or 8 weeks (n=4 rats) were MR imaged on a Bruker Pharmascan 4.7T magnet with a home-built bird-cage coil. T2 was quantified by using a mono-exponential fitting algorithm on multi-slice multi echo T2 weighted data. Statistical comparison was performed using ANOVA. Results: (I) Histopathologic evaluation of both rat and human livers demonstrated no evidence of steatosis or hemochromatosis There was a monotonic increase in mean T2 value with increasing degree of fibrosis (control 65.4±2.9 ms, n=6 patients); mild (Ishak 1–2) 66.7±1.9 ms (n=30); moderate (Ishak 3–4) 71.6±1.7 ms (n=26); severe (Ishak 5–6) 72.4±1.4 ms (n=61); with relatively low standard error (~2.9 ms). There was a statistically significant difference between degrees of mild (Ishak 4) (P=0.03) based on logistic regression of T2 and Ishak, which became insignificant (P=0.07) when using inflammatory markers as covariates. Expanding on this model using ordinal logistic regression, there was significance amongst all 4 groups comparing T2 to Ishak (P=0.01), with significance using inflammation as a covariate (P=0.03) and approaching statistical significance amongst all groups by ANOVA (P=0.07). (II) There was a monotonic increase in T2 and statistical significance (ANOVA P